2021
DOI: 10.1016/j.tranon.2020.100950
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1 and the TNFα axis as a targetable mediator of liver injury from stereotactic body radiation therapy

Abstract: Highlights Elevated soluble TNFR1 levels are predictive of liver toxicity among patients receiving radiation. Soluble TNFR1 levels do not independently predict liver toxicity when included in models with ALBI and mean liver dose. Data suggest that liver inflammation mediates toxicity after liver irradiation and that the TNFα axis is associated with this inflammation. Future studies of should evaluate approaches that target pre-treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…A divergent activity of pro-inflammatory cytokines, such as tumor necrosis factor α, was noted between HCC patients of different CTP scores at baseline and early during liver SBRT. 35,36 This variable cytokine profile by liver function was suggested to mediate the differential radiation sensitivity of the liver and the development of liver toxicity, thereby affecting survival. In this cohort, the baseline CTP class was identified as the only predictor of dNLR after SBRT, and the difference in dNLR between CTP groups mainly arises from the post-SBRT change.…”
Section: Discussionmentioning
confidence: 99%
“…A divergent activity of pro-inflammatory cytokines, such as tumor necrosis factor α, was noted between HCC patients of different CTP scores at baseline and early during liver SBRT. 35,36 This variable cytokine profile by liver function was suggested to mediate the differential radiation sensitivity of the liver and the development of liver toxicity, thereby affecting survival. In this cohort, the baseline CTP class was identified as the only predictor of dNLR after SBRT, and the difference in dNLR between CTP groups mainly arises from the post-SBRT change.…”
Section: Discussionmentioning
confidence: 99%
“…20-70 min) [82] as plasma samples were generated before and after the completion of radiotherapy. Interestingly, two other studies that investigated plasma levels of TNFα receptors over the course of radiotherapy found a correlation with the development of liver toxicity [45,46]. Cousins and colleagues found an association between liver toxicity and TNFR1, while Ng and colleagues found an association with mid-treatment TNFR2 levels.…”
Section: Commenmentioning
confidence: 99%
“…Potential Predictive Scores/Biomarkers ALBI [23][24][25][26][27]29] ALBI [23][24][25]29,39] Absolute lymphocyte count [43] Indocyanin Green Retention [35][36][37] Hepatocyte growth factor (HGF) [40,41] HGF [40,41] CD40 Ligand (CD40L) [45] sCD40L [40,45] Platelet-to-lymphocyte ratio [43] Transforming growth factor (TGF)-β [42] Neutrophile-to-Lymphocyte ratio [43,50,53] Neutrophile-to-Lymphocyte ratio [53] Interleukin 6 (IL-6) [43,44] Eotaxin [42] Interleukin 10 (IL-10) [44] TNF receptor I (TNFR-I) [46] Tumor Necrosis Factor receptor II [45] TNFR-II [45] Circulating lymphocyte counts [47,[49][50][51][52] Circulating lymphocyte counts [49] Tumor Necrosis Factor (TNF)-α [51] Micro RNAs [101] Cell-free DNA [90] Plasma metabolites [98] Ceramide [99] Programmed cell d...…”
Section: Potential Prognostic Scores/biomarkersmentioning
confidence: 99%
“…Studies of liver toxicity after SBRT have shown that pretreatment levels of HGF and sTNFR1, predict hepatic injury after treatment (13)(14)(15). Additionally, baseline cytokine levels and inflammation-related lab values predict overall survival, suggesting even broader potential application of pretreatment lab-based studies (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…relationships between markers and baseline liver status, risk of liver toxicity, local disease progression, systemic disease, and/or comorbid conditions). We have previously proposed that select cytokines portend an inflammatory state that could be targeted with the goal of reducing toxicity following radiation (13). Prior studies of hepatotoxicity and survival following radioembolization have focused on dose-metrics and liver function assessment, but some have considered blood cytokine levels (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%